Effect of organic fertilizers on the cultivation of Theobroma cacao L. in the nursery of "Recinto el Capricho", Province of Napo, Ecuador - Cuvi Ramírez, María Beatriz (2013)
The research was performed using an improved soil mixture using four types of manures and compost plus a control in the propagation of Theobroma cacao L. seedlings in a tree nursery, with the hypothesis that the principal factor in seedling development is the substrate. In this study, the growth was analyzed using the following physiological indicators: germination rate, plant height, stem diameter and survival rate of two different types of nursery covers (saran and greenhouse plastic) was analyzed by the research farm Recinto “El Capricho“ in the province of Napo. The best treatment for germination rate was a mixture of forest soil, sand and worm humus under saran of soil, sand, and compost greenhouse plastic. These two treatments resulted in a germination rate of 100 %. The best substrate for plant height and stem diameter was a mix of forest soil, sand and guinea pig manure. This treatment resulted in an average plant height of 35 cm and a stem diameter of 8,72 mm under the plastic cover.